Supplier selection based on multi-stakeholder Best- Worst Method - Fallah Lajimi, Hamidreza; Seyed Haeri, Seyed Amin; Jafari Sorouni, Zahra; Salimi, Negin (Journal of Supply Chain Management Science, 2021)
Supplier selection and supplier segmentation are two interdependent crucial steps of effective supplier relationship management. Supplier selection is formulated as a multi-criteria decision-making problem, in which evaluation criteria play a critical role in a realistic assessment of the suppliers. The evaluation criteria can be used to link supplier selection and segmentation steps to have a more efficient and effective supplier relationship management. A multi-stakeholder Best-Worst Method (BWM) is used for supplier selection. The proposed method is a proper tool to handle the optimal weights of the BWM, which are in the form of intervals. The proposed approach enables decision-makers to avoid information loss within their decision-making procedure resulting in more realistic decisions. A real-world case study is used to illustrate the proposed decision-making framework. The final results show the best suppliers based on both capabilities and willingness dimensions which can be selected by the case company.